PENGARUH PRAKTIKUM ELEPHANT TOOTHPASTE DALAM PEMBELAJARAN GUNUNG BERAPI TERHADAP SOSIAL EMOSIONAL SISWA KELAS 8 SMPN 3 MALANG - Selvi Dewi Nur Anggreani (Jurnal Pembelajaran, Bimbingan, dan Pengelolaan Pendidikan, 2024)
This study aims to explore the influence of Elephant Toothpaste experiment in volcano learning on the social-emotional aspects of 8th-grade students at SMPN 3 Malang. Quantitative method was employed by analyzing students' expressions and utterances during the experiment. The results indicated that the majority of students exhibited positive social-emotional expressions, including enthusiasm, collaboration, and high curiosity. Integrating social-emotional education into science learning positively impacted the classroom atmosphere and students' learning outcomes. These findings underscore the importance of holistic learning that addresses students' social-emotional aspects. However, variations in social-emotional expressions highlight the need for more inclusive teaching strategies. This research provides a foundation for the development of learning approaches that support students' social-emotional development.